2005
DOI: 10.1097/01.aog.0000181821.82022.82
|View full text |Cite
|
Sign up to set email alerts
|

Birth Outcomes in Obese Women After Laparoscopic Adjustable Gastric Banding

Abstract: II-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(157 citation statements)
references
References 31 publications
5
143
1
8
Order By: Relevance
“…We also aimed to study the frequencies of hypertension/preeclampsia and diabetes during pregnancy but found no differences. This result is in accordance with earlier findings on pregnancy outcome after bariatric surgery (9,28).…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…We also aimed to study the frequencies of hypertension/preeclampsia and diabetes during pregnancy but found no differences. This result is in accordance with earlier findings on pregnancy outcome after bariatric surgery (9,28).…”
Section: Commentsupporting
confidence: 93%
“…There are several studies that have evaluated obstetric outcome after bariatric surgery (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Dixon et al provided a prospective study of 79 women who became pregnant after LAGB. The pregnancy outcomes (pregnancy induced hypertension (PIH), gestational diabetes, stillbirths, preterm deliveries, IUGR, and high birth weight) were consistent with general community outcomes [15].…”
Section: Literaturesupporting
confidence: 53%
“…4,[18][19][20] Our findings suggest that women who are able to lower their prepregnancy BMI, even if it is only from superobese to morbidly obese, may decrease their risk of cesarean delivery, neonatal hypoglycemia, and composite neonatal morbidity. For a 5′4″ woman, a change in weight of 5.9 lbs corresponds with a 1 unit change in BMI.…”
Section: Commentmentioning
confidence: 73%